A study of complementary feeding practices among higher educated mothers in north-western part of Rajasthan - Pansari, Vishnu Kumar; Verma, Suniti Verma; Sehra, Ram Narain; Nagaraj, Niranjan (Indian Journal of Child Health, 2022)
Background: Infants and young children are at an increased risk of malnutrition from 6 months of age onward when breast milk alone is no longer sufficient to meet all their nutritional requirements and complementary feeding should be started. Objective: This study was undertaken to assess the practices of complementary feeding and knowledge of infant milk substitute (IMS) act in higher educated mothers. Materials and Methods: This hospital-based cross-sectional descriptive study was conducted in a medical college of Rajasthan from January to December 2015. Totally, 300 mothers with graduate/post-graduate degree whose children were between 9 and 15 months of age,were included in the study. All the mothers were interviewed as per the standardized pro forma regarding the complementary feeding practices. Results: Maximum numbers of mothers were homemakers (67.3%) as compared to employed (32.7%). In the present study, 38.98% mothers practiced exclusive breastfeeding till 6 months of age, and 69.49% infants were exclusive breastfed till 4 months of age. Out of total 300 mothers, 116 (38.6%) introduced complementary feed before 6 months of age while 142 (47.3%) introduced at 6 months of age. 140 (46.6%) educated mothers started complementary feeding with homemade preparations while 115 (38.4%) started with market preparations. 33 (39.2%) mothers stopped breastfeeding at 6-9 months of age, and 33 (39.2%) mothers stopped breast feeding between 10 and 12+ months of age. A significant portion 274 (91.3%) of educated mothers did not have knowledge of IMS act. Conclusion: In the present study, majority of the mothers considered milk supplementation as complementary feeding and employed mothers preferred market preparations. Knowledge regarding IMS act was not satisfactory.